Small farmers’ preferences for weather index insurance: insights from Kenya - Sibiko, Kenneth W.; Veettil, Prakashan C.; Qaim, Matin (Springer, 2018)
Smallholder farmers in developing countries are particularly vulnerable to climate shocks but often lack access to agricultural insurance. Weather index insurance (WII) could reduce some of the problems associated with traditional, indemnity-based insurance programs, but uptake has been lower than expected. One reason is that WII contracts are not yet sufficiently tailored to the needs and preferences of smallholder farmers. This study combines survey and choice-experimental data from Kenya to analyze the experience with an existing WII program and how specific changes in the contractual design might encourage uptake Many smallholders struggle with fully understanding the functioning of the program, which undermines their confidence. Regular provision of relevant rainfall measurements and thresholds would significantly increase farmers’ willingness to pay for WII. Mechanisms to reduce basis risk are also positively valued by farmers, although not to the same extent as higher levels of transparency. Finally, offering contracts to small groups rather than individual farmers could increase insurance uptake Better training on WII and regular communication are needed. Group contracts may help to reduce transaction costs. Farmer groups can also be important platforms for learning about complex innovations, including novel risk transfer products. These concrete results are specific to Kenya; however, they provide some broader policy-relevant insights into typical issues of WII in a small-farm context.